Patterns of p21waf1/cip1 expression in non-papillomatous nasal mucosa, endophytic sinonasal papillomas, and associated carcinomas. Issue 11 (1st November 2001) - Schwerer, M J; Sailer, A; Kraft, K; Baczako, K; Maier, H
Abstract : Aims —To clarify p21 waf1/cip1 expression in sinonasal lesions. Methods —Archived surgical specimens from 38 patients were investigated by means of immunohistochemistry. p21 waf1/cip1 staining was evaluated in the different layers of the epithelium. In addition, human papillomavirus (HPV) infection and p53 protein overexpression were assessed and correlated with p21 waf1/cip1 expression. Results— p21 waf1/cip1 staining was negative in non-papillomatous nasal mucosa. HPV infection and p53 protein overexpression were not seen. Sixteen of 20 inverted papillomas showed p21 waf1/cip1 expression. HPV infection was found in 16 cases and p53 protein overexpression was present in 13 specimens. Expression of p21 waf1/cip1 was restricted to surface cells in five cases, but involved basal/parabasal cells in 11 specimens. Immunoreactivity for p21 waf1/cip1 in basal/parabasal cells colocalised with p53 protein overexpression. Enhanced expression rates for p21 waf1/cip1 were seen in transitional and squamous epithelium compared with columnar epithelium. p21 waf1/cip1 expression involved only surface cells in cylindrical cell papillomas. HPV infection and p53 protein overexpression were detected in all specimens. One of five squamous cell carcinomas showed p21 waf1/cip1 expression. HPV infection was seen in two cases, and all carcinomas showed p53 protein overexpression. Conclusions —Expression of p21 waf1/cip1 is associated with terminal differentiation in surface cells in inverted papillomas and cylindrical cell papillomas, but not in non-papillomatous nasal mucosa. Overexpression of p53 protein colocalises with p21 waf1/cip1 expression in basal/parabasal cells in inverted papillomas but not in cylindrical cell papillomas. Expression of p21 waf1/cip1 in squamous cell carcinomas involves a subset of tumours with p53 protein overexpression.